Perbandingan Waktu Pengisian Baterai Pada Pembangkit Listrik Tenaga Surya Antara Dua Tempat Berbeda (Studi Kasus: Kota Medan dan Desa Kabung Kecamatan Barus Jahe) - Sitepu, Bernike Patresia; Siagian, Parlin; Dino Erivianto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
A potential avenue for the utilisation of solar energy is through the establishment of a PLTS (solar power plant). The present study employs an experimental approach in two distinct locations to ascertain the voltage and current of a battery that has been charged by a 20 Wp solar panel of polycrystalline type. Additionally, the temperature and humidity at each location are measured. The research location is situated in Kabung Village, within the administrative boundaries of Medan City. The research period spanned six days, from April 27 to May 3, 2025. A series of measurements were conducted over the course of the day, commencing at 09:00 WIB / 16:00 WIB. The data was collected at 10-minute intervals and comprised a combination of voltage, current, temperature, and humidity measurements. These measurements were obtained from two distinct locations within the city and the village. The mean battery charging time in Medan city is 6.50 hours, with a voltage of 12.26 volts, a current of 0.23 Ampere, a temperature of 33.14 °C and a humidity of 72.2%. In the context of Kabung village, the mean battery charging time was determined to be 6.50 hours, with a recorded voltage of 12.92 volts, a current of 0.60 Ampere, a temperature of 40.17 °C and a relative humidity of 63.3%. This study provides significant insights into the impact of geographic location on the performance of PLTS, particularly with regard to the optimal levels of sunlight absorption. Whilst the duration of battery recharge remains unaltered in this instance, the probability of attaining a greater quantity of electrical energy within a reduced timeframe is more probable in locales exhibiting elevated levels of sunlight, such as Kabung Village.